REPRESENTASI OBJEKTIVIKASI SEKSUAL PADA PEREMPUAN DI DUNIA MAYA DALAM FILM LIKE AND SHARE (Analisis Wacana Kritis Sarah Mills) - Suwito, Afdholul Arrozy; Rusmana, Dewi Sri Andika; Rizqi, Muchamad (Sintesa, 2025)
This study aims to analyze the representation of sexual objectification of women in cyberspace as depicted in the film Like and Share, directed by Gina S. Noer. The film was chosen for its explicit portrayal of sexual explotation, non-consensual distribution of intimate content, and its impact on women in the digital era. The research applies Sara Mills Model of Critical Discourse Analysis, which focuses on subject positioning within texts, power relations, and their connection to broader social structures. Stuart Hall theory of representation is used to explore how meanings surrounding women’s bodie and sexuality are constructed and produced through cinematic language. The findings reveal that women in the film are portrayed as sexual objects through the camera gaze, character narratives, and the influence of social media. However, thefilm also positions women as active subjects who develop awareness and resist various forms of objectification. Thus, Like and Share not only reproduces dominant meanings regarding female sexuality but also creates a space for critique and reflection on patriarchal digital culture